URGENSI PERMOHONAN PENETAPAN WALI OLEH ORANG TUA UNTUK PENJUALAN HARTA ANAK PERSPEKTIF UNDANG UNDANG PERLINDUNGAN ANAK - Raden Muyazin Arifin; Hafis Baraas (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
Minors need the help of guardians to carry out legal acts, including the transaction of children's property. In Indonesian laws, parents have the right to be the guardians of their children and when acting as guardians all the actions they do must be in the best interests of their children. The prominent number of domestic violence against children, especially those committed by parents, deserves attention. Parents have obligations and responsibilities to their children, including child protection. To exercise their rights as guardians, parents must properly fulfill their obligations and responsibilities towards their children. Therefore, the appeal for guardianship through court is important as a means of verification whether parents have properly fulfilled their obligations and responsibilities. In this study, the first core problem is